Elektif ve acil sezaryen ameliyatlarında anestezi yönetimimiz: Son on yılın retrospektif değerlendirilmesi - Özmen, Özgür; Arslan, Zakir; Ekinci, Mürsel; Tör, İbrahim; Kara, Duygu; Karakaya, Muhammet Ahmet (Logos Medical Publishing, 2016)
Sezaryen ameliyatlarında kullanılan anestezi uygulaması seçi- mi; hastanın kliniği, anestezistin tecrübesi, cerrahinin aciliyeti ve hastanın isteğine göre belirlenir. Bu çalışmada, kadın doğum hastanemizde son 10 yılda yapılan sezaryen operasyonlarındaki anestezi uygulamaları değerlendirilmiştir. 2006-2015 yılları ara- sında hastanemiz bilgisayar sistem kayıtları ve dosya arşivleri tarandı. Elektif ve acil olarak yapılan sezaryen ameliyatlarında kullanılan anestezi yöntemleri kaydedildi. Bu yöntemlerin yılla- ra göre dağılımı analiz edildi. Hastanemizde 2006-2015 yılları arasında toplam 28986 sezaryen ameliyatı gerçekleştirilmiştir. Sezaryenlerin %84’ü acil, %16’sı elektifti. Dört bin sekiz yüz kırk sekiz (%17) hastada genel anestezi, 24138 (%83) hastada böl- gesel anestezi tercih edilmiş olup, hastaların %2’sinde kombine spinal-epidural, %1’inde ise epidural anestezi tercih edilmiştir. Kliniğimizde bölgesel anestezi yöntemlerinin kullanımı Avru- pa ülkelerine benzer şekilde yüksek bulunmuştur. Kliniğimizde bölgesel anestezi yontemi olarak en Çok spinal anestezi tercih edilirken, özellikle acil vakalarda hiç kombine spinal-epidural ve epidural anestezi uygulanmadığı görülmektedir. Elektif va- kalarda ise kombine spinal-epidural uygulamasının artırılması gerektiği düşüncesindeyiz.

The choice of anesthesia used in cesarean operations is determined by the patient’s clinical status, the experience of the anesthetist, the urgency of surgery and the patient’s wishes. This study evaluated anesthetic practices in cesarean surgery performed in the preceding 10 years in our Maternity Hospital, Turkey. Hospital computer system records and file archives between 2006 and 2015 were screened. Anesthesia techniques used in elective and emergency cesarean surgery were recorded. The distribution of these techniques by years was then analyzed. A total of 28.986 cesarean sections (cases) were performed in our hospital in 2006-2015. Eighty-four percent of them were emergency and 16% of them were elective CSs. General anesthesia was used in 4848 (17%) and regional anesthesia in 24.138 (83%) patients, while combined spinal-epidural anesthesia was used in 2% and epidural anesthesia in 1% of the patients. Regional anesthesia was used frequently in our clinic similar to European countries. Spinal anesthesia was the most commonly preferred method of regional anesthesia in our clinic. However, especially in emergency cases combined spinal-epidural or epidural anesthesia was not applied. We think that combined spinal-epidural anesthesia should be applied more frequently in elective cases.
Our management of anesthesia in elective and emergency cesarean surgery: A retrospective evaluation of the last ten years
Keywords: Bölgesel Anestezi; Obstetrik Anestezi; Retrospektif Çalışma; Regional Anesthesia; Obstetric Anesthesia; Retrospective Study